The Contribution of Causal-Comparative Quantitative Method to the Quality of Educational Research - Purba, Nurhaibah; Ramanda, Yusnita; Nasution, Diah Umiati (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the contribution of the causal-comparative quantitative research method to the quality of educational research. The causal-comparative quantitative method is used to assess cause-and-effect relationships between variables in an educational context without conducting experimental manipulation. This approach allows researchers to compare different groups and evaluate the influence of specific factors on educational outcomes. Data were collected through a literature review and analysis of various educational studies employing the causal-comparative method. The findings indicate that this method significantly contributes to enhancing the validity, reliability, and accuracy of interpreting educational research results. The study recommends the use of the causal-comparative method as an effective strategy for achieving high-quality research outcomes in education.